PENGGUNAAN REDUKSI KETIDAKPASTIAN KETIKA MEMULAI HUBUNGAN DALAM APLIKASI ONLINE DATING DI INDONESIA - Rahmat, Alyssa Melita; Irwansyah, Irwansyah (Ilmu Komunikasi, FISIP Universitas Pasundan, 2021)
Along with the development of technology and the ease of communicating, there is a significant rise of using online dating application not only in global scope but also in Indonesia. However, in this ease of communicating, there is a problem that arose and become a barrier in the development of an online relationship. Uncertainty of an information found in the online dating applications be the focus of this study. Using Uncertainty Reduction Theory, this study explains how uncertainty that was found in the use of online dating application can be reduced by using three strategies in seeking information that was developed by Charles Berger and Richard Calabrese. This study uses qualitative approach with the method of literature review which compiles various journals and theses that were obtained through Google Scholar in the range of year 2010 – 2020. The result of this study shows that Uncertainty Reduction Theory has a significant role in reducing the uncertainty of information or dating profiles that were found in the use of online dating application in Indonesia.